2011
DOI: 10.5402/2011/130289
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide: Modes of Action and Possible Impact on Nontarget Microorganisms

Abstract: Fungicides have been used widely in order to control fungal diseases and increase crop production. However, the effects of fungicides on microorganisms other than fungi remain unclear. The modes of action of fungicides were never well classified and presented, making difficult to estimate their possible nontarget effects. In this paper, the action modes and effects of fungicides targeting cell membrane components, protein synthesis, signal transduction, respiration, cell mitosis, and nucleic acid synthesis wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
129
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(139 citation statements)
references
References 63 publications
2
129
0
8
Order By: Relevance
“…Fungicides may also impact cellular immunity in cases where mitochondria modulate cell death and innate immune signaling (Arnoult et al 2009). An alternative explanation for the sublethal effects of Pristine® on protein digestion and immunity might be that the fungicide altered the composition and diversity of gut microbial communities that may contribute to pollen digestion and pathogen defense (Babendreier et al 2007;Engel et al 2012;Koch and Schmid-Hempel 2011;Yang et al 2011). Though bacteria do not have mitochondria, electron transport occurs in the cell membrane and uses ubiquinone and cytochrome b as electron carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Fungicides may also impact cellular immunity in cases where mitochondria modulate cell death and innate immune signaling (Arnoult et al 2009). An alternative explanation for the sublethal effects of Pristine® on protein digestion and immunity might be that the fungicide altered the composition and diversity of gut microbial communities that may contribute to pollen digestion and pathogen defense (Babendreier et al 2007;Engel et al 2012;Koch and Schmid-Hempel 2011;Yang et al 2011). Though bacteria do not have mitochondria, electron transport occurs in the cell membrane and uses ubiquinone and cytochrome b as electron carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in vitro toxicity analysis of propiconazole on human cell lines authenticates its toxicity (Satapute and Kaliwal, 2015). Conversely, Yang et al (2011) and Niewiadomska and Maruwka (2011) have reported that, propiconazole will have the greatest impact to inhibit the bacterial activity in the wetlands.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini tidak hanya menyebabkan naiknya biaya produksi melalui pembelian fungisida, namun juga meningkatkan kerusakan lingkungan serta risiko gangguan terhadap kesehatan tubuh (Verweij et al, 2009;Yan et al, 2011).…”
Section: Pendahuluanunclassified